A Reflection on the Current State of Active Learning Research - Amedee Marchand Martella; Darryl Schneider (Journal of the Scholarship of Teaching and Learning)
Interest in active learning continues to grow worldwide. Although the large volume of active learning research has provided a myriad of ways to implement active learning in the classroom, the construct remains underdeveloped and difficult to operationalize because of three main issues in the research literature: (a) the variation in active learning activities in research and in practice; (b) the dichotomy between active learning and lecture; and (c) whether “active” in active learning refers to behavioral activity, cognitive activity, or both. The purpose of this reflection article is to articulate these issues so that active learning can move beyond its current status as a “curious construct.” By discussing avenues for future research that address those issues, our goal is to move the field forward by helping researchers focus on why active learning is effective, which forms of it are the most effective, how it should be implemented to maximize learning, and for whom different active learning interventions are the most effective. Just as active learning is easy to prescribe, it should also be easy to implement.